Governance and Fund Management in the Chinese Pension System - Hu, Yu-Wei (IMF Working Papers; Working Paper ;, 2009)
The Chinese pension system is highly fragmented and decentralized, with governance standards, pension fund management practices, their regulation and supervision varying considerably both across the funded components of the Chinese pension system and across provinces. This paper describes the key components of the system, highlights the progress made to date and identifies remaining weaknesses, in regard to information disclosure, the governance framework and pension fund management standards.